2013
DOI: 10.4028/www.scientific.net/amr.668.65
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Research on Alkali-Activated Slag Concrete as Tunnel Lining in Severe Frigid Regions

Abstract: The main structure materials of tunnel lining are concrete and steel, and the concrete frost damage is a typical degradation phenomenon of the tunnel linings in cold regions. Alkali-activated slag concrete (ASC) has a better freeze-thaw resistance, which can be used for tunnel lining in severe frigid regions. Freeze-thaw resistance, performance mechanism of ASC and microstructure were investigated by freeze-thaw cycle, X-ray diffraction (XRD) and Scanning electron microscope (SEM) analysis. The experimental re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Similar conclusions have been reported for fly ash mortars, in comparison to OPC-based specimens. 79 Shu 80 reported that AAS concrete showed excellent freeze− thaw resistance, thus fitting their application in tunnel lining in extremely cold regions. It was also shown that, using a blend of fly ash and slag in concrete synthesis, the relative dynamic modulus was ∼90% after 300 freeze−thaw cycles with a slight mass loss and physical deterioration due to thin surface layers that favorably restrain freeze−thaw damage of concrete.…”
Section: Durabilitymentioning
confidence: 94%
“…Similar conclusions have been reported for fly ash mortars, in comparison to OPC-based specimens. 79 Shu 80 reported that AAS concrete showed excellent freeze− thaw resistance, thus fitting their application in tunnel lining in extremely cold regions. It was also shown that, using a blend of fly ash and slag in concrete synthesis, the relative dynamic modulus was ∼90% after 300 freeze−thaw cycles with a slight mass loss and physical deterioration due to thin surface layers that favorably restrain freeze−thaw damage of concrete.…”
Section: Durabilitymentioning
confidence: 94%
“…It was also found that air-entraining admixtures commonly used to increase the freeze-thaw durability of Portland cement concrete did not increase the durability of alkali activated fly ash materials. Heng [21] reported that alkali activated slag concrete showed excellent freeze-thaw resistance, thus fitting their application in tunnel lining in extremely cold regions.…”
Section: Introductionmentioning
confidence: 99%